Volume at First Leak Is Associated With Sling Failure Among Women With Stress Urinary Incontinence. Issue 4 (July 2019) - Hill, Bryan; Fletcher, Sarah; Blume, Jeffrey; Adam, Rony; Ward, Renée
Abstract : Introduction: Stress urinary incontinence at a low bladder volume is a clinically observed phenomenon that is not well studied with regard to treatment outcomes. The primary aim of our study was to determine if the volume at first leak is associated with sling outcome. Methods: This is a retrospective cohort study evaluating whether urodynamic stress urinary incontinence observed at low volumes is associated with sling failure using the Synthetic Derivative database. Sling failure was defined as (1) undergoing a subsequent surgery for stress incontinence (eg, urethral bulking agent, repeat sling) or (2) leakage that was subjectively worse or unchanged from baseline. Sling success was defined as subjective improvement in incontinence or being dry. Intrinsic sphincter deficiency was defined as maximum urethral closure pressure 20 cm H2 0 or less or abdominal leak point pressure less than 60 cm H2 0. Results: Outcome data were available for 168 of 206 women who underwent a sling after urodynamic testing from 2006 to 2014. Of the 168 women, 80 were transobturator, 79 were retropubic, 8 lacked data regarding the approach to the midurethral sling, and 1 was an autologous pubovaginal sling. Similar failure rates were seen for transobturator (10%) and retropubic slings (7.6%). Preoperative urodynamic parameters, such as cystometric capacity and intrinsic sphincter deficiency, were similar among failed and successful slings. For every additional 50 mL in bladder volume at first leak (SUIvol ), there was a 1.6 increased odds of having a successful sling (odds ratio, 1.576; 95% confidence interval, 1.014–2.450; P = 0.04). There was no statistically significant association between maximum urethral closure pressure, abdominal leak point pressure, body mass index, age, sling type, or whether a prior anti-incontinence procedure had been performed and sling success. Conclusions: Bladder volume at first leak is a strong predictor of sling failure.